AN ANALYSIS OF TEACHER FACTORS IN ASSISTING STUDENTS IN THEIR LEARNING - Nugraheni, Mutia Farisya Sekar; Nuranda , Ilham; Perkasa , Pradana Gilang (Verba: Journal of Applied Linguistics, 2024)
This study explores the influence of teacher-related factors on assisting students in tutoring environments. It specifically examines how teachers' educational backgrounds and training affect student performance. Conducted in a tutoring centre in Semarang City, Indonesia, the research utilised a descriptive qualitative approach with semi-structured interviews of two teachers. The findings reveal that most teachers possess relevant educational backgrounds for their subjects, which is essential for effective teaching. Furthermore, the institution's training process, which includes a probation period for new teachers, ensures they are well-prepared to meet students' learning needs. The study concludes that teacher factors, especially educational background and training, significantly enhance student learning outcomes in tutoring settings. The results indicate that the institution's methods for selecting and training teachers are effective, emphasising the importance of these factors in educational contexts